A Theory of Rational Jurisprudence - Baker, Scott; Mezzetti, Claudio (Journal of Political Economy, 2012)
We examine a dynamic model of up-or-down problem solving. A decision maker can either spend resources investigating a new problem before deciding what to do or decide on the basis of similarity with precedent problems. Over time, a decision-making framework, or jurisprudence, develops. We focus on the model’s application to judge-made law. We show that judges summarily apply precedent in some cases. The law may converge to efficient or inefficient rules. With positive probability, identical cases are treated differently. As the court learns over time, inconsistencies become less likely. We discuss the existing empirical evidence and the model’s testable implications.